Video Dokumenter Penggunaan Media Online pada Waria di Kecamatan Sapeken Mengonsumsi Suplemen Kulit - Zarnuji Wiraraja; Ach. Andiriyanto; Deny Feri Suharyanto (Jurnal Desain Komunikasi Visual Asia, 2023)
Although geographically and socio-culturally the drag queens on the Island / Sapeken Village live within limitations. However, they continue to try to show their existence as the third gender in society. One of them is by taking care of the skin so that it still looks healthy and bright. This study aims to determine the use of online media in waria in Sapeken District in consuming skin supplements. The main characteristics of online media are interconnectedness, access to individual audiences as recipients and senders of messages, interactivity, diverse uses as open characters, and their ubiquitous nature. The basis of this research is descriptive qualitative. This is a series of procedures in an effort to solve the problem under study by describing the object of research based on real facts. This research report contains excerpts of data that give an idea of the presentation of the report. The final value conclusion is 93% with the success rate of "Excellent", the results of the audience of the transgender documentary video on Sapeken Island consider it with easy information to understand.